Probiotics for Preventing Relapse in Ulcerative Colitis: A Systematic Review and Bayesian Network Meta-Analysis - Alvianto, Steven; Muzellina, Virly Nanda; Widjanarko, Nicolas Daniel; Lee, Yeong Yeh; Wangidjaja, Olivia (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease characterized by periods of relapse and remission. Preventing relapse is critical to improving long-term outcomes. This study aimed to compare the efficacy of probiotics, 5-aminosalicylic acid (5-ASA), probiotics combined with 5-ASA, and placebo in preventing relapse in UC.Methods: A comprehensive search from PubMed, Cochrane Library, MEDLINE, ProQuest, ScienceDirect, Clinical Trials. gov and Google Scholar databases were conducted. The primary outcome was clinical relapse. A Bayesian random-effects model calculated pooled odds ratios (ORs) with 95% CIs and treatment ranks were assessed using the surface under the cumulative ranking curve (SUCRA).Results: Of total 552 initial papers, 37 extracted, and 26 were removed due to exclusion criteria. Eleven RCTs involving 1,099 participants were eventually included for analysis. Probiotics combined with 5-ASA had the highest efficacy (OR = 0.23, 95% CI: 0.027–1.09; SUCRA = 71.43), followed by 5-ASA alone (OR = 0.25, 95% CI: 0.035–0.95; SUCRA = 66.90) and probiotics alone (OR = 0.275, 95% CI: 0.059–0.724; SUCRA = 59.69). Placebo ranked lowest (SUCRA = 1.98). The most commonly used probiotics included E. coli Nissle 1917, Lactobacillus GG, and Bifidobacterium species. The most frequently used 5-ASA preparation was mesalazine. Interventions were generally well-tolerated, with no significant adverse events reported. Conclusion: With the Bayesian NMA, Probiotics plus 5-ASA demonstrates the highest efficacy in preventing relapses in UC. Further research is needed to standardize probiotic regimens and to assess long-term outcomes with the combination approach.